A predicted three-dimensional structure for the human immunodeficiency virus binding domains of CD4 antigen. - Bates, P; McGregor, M; Islam, SA; Sattentau, Q; Sternberg, M (1989)
A predicted three-dimensional structure of the two N-terminal extracellular domains of human CD4 antigen, a cell surface glycoprotein, is reported. This region of CD4, particularly the first domain, has been identified as containing the binding region for the envelope gp120 protein of the human immunodeficiency virus. The model was predicted based on the sequence homology of each domain with the variable light chain of immunoglobulins. The framework beta-sheet regions were taken from the crystal coordinates of REI. For one region in the first domain of CD4 there was an ambiguity in the alignment with REI and two alternate models are presented. Loops connecting the framework were modelled from fragments selected from a database of main chain coordinates from all known protein structures. Residues identified as involved in binding gp120 have been located in several other studies within the first domain of CD4. Epitopes from eight monoclonal antibodies have been mapped onto residues in both domains. Competition of these antibodies with each other and with gp120 can be interpreted from the structural model.